Efficacy of several digital radiographic imaging systems for laboratory determination of endodontic file length - Oliveira, M. L.; Ambrosano, G. M. B.; Almeida, S. M.; Haiter-Neto, F.; Tosoni, Guilherme Monteiro [UNESP] (Wiley-Blackwell, 2011)
P>AimTo compare the efficacy of different digital radiographic imaging systems for determining the length of endodontic files.MethodologyK-type endodontic files were introduced into the canals of 40 extracted human permanent single-rooted teeth and fixed in place at random lengths. The teeth were radiographed using Digora Optime (R), CygnusRay MPS (R) and CDR Wireless (R) digital imaging systems. Six observers measured every file length in all the images and repeated this procedure in 50% of the image samples, and assigned a score to the level of difficulty found. Analysis of variance for differences between digital systems and Tukey's test were performed. The level of intraobserver agreement was measured by intraclass correlation. The assigned scores were evaluated by Kruskal-Wallis and Dunn's tests.ResultsThe CDR Wireless values did not differ significantly from the actual lengths and the CygnusRay MPS values. The Digora Optime system was significantly different from the others and overestimated the values (P < 0.05). The Digora Optime was significantly easier to use for taking measurements and the CygnusRay MPS the most difficult (P < 0.05). All digital radiographic imaging systems showed excellent agreement with the Intraclass Correlation Coefficient > 0.95.ConclusionsThe three digital radiographic imaging systems were precise. The CDR Wireless system was significantly more accurate in determining endodontic file lengths, and similarly to Digora Optime, was considered the least difficult to use when assessing endodontic file lengths.
Keywords: digital dental radiography; endodontics; odontometry; software